Archieve Media Promotion for Collective Memory Safety on Digital Natives Generations - muhammad, rom ubaidillah; Anwary, Ahdie (Record and Library Journal, 2019)
Background of the study: Archives as a collective memory of a nation make it important to be managed and disseminated to all Indonesian people, especially in the current generation of Indonesian youth, namely the generation of digital natives. The generation of young people being the successors of the Indonesian nation's struggle must know the long history of the social history of the people in Indonesia through archives. The government has made a solution through a conscious archive movement but in reality the conscious socialization of the archives seems to not be heard in the community especially by the generation of digital natives. Access to archives carried out domestically in ANRI's annual report in 2015-2016 shows that in 2015 there were 5,215 people and in 2016 there were 4,747, a decline in 2016 regarding access to archives.Purpose: This study aims to provide recommendations regarding the use of promotional media that can be carried out by ANRI institutions in maintaining the nation's collective memory, especially towards the generation of digital natives.Method: This paper uses a literature review method with data collection of various materials contained in the library, such as newspapers, books, magazines, manuscripts, documents and so on that are relevant to research with theoretical studies and literature.Findings: The results of this study indicate that the promotional media that is right for use by ANRI in promoting archives is through social media and media mobile phone applications based on the way of interaction of the generation of digital natives.Conclusion: With this research, it is expected that ANRI as the highest institution managing state archives can consider the importance of promotion for archives and utilizing promotional media for the general public, especially in the generation of digital natives